Prototyping a remotely-controlled machine for concrete surface grinding operations - Moon, Sungwoo; Kim, Jeonghwan; Seo, Jongwon (Journal of Civil Engineering and Management, 2017)
The surface of concrete pavement needs to be flattened for the smoothness and comfortability of highways. Surface grinding can provide flatness in the hardened concrete surface, and improve adhesion between the existing concrete surface and the subsequent layer. The surface grinding process, however, is executed under hazardous work conditions and the outcome is affected by a machine operator’s skill. Automation of this process can provide a hazard-free work environment and increase the quality of the ground surface. This paper presents an application of an automated concrete surface grinding machine that an operator can remotely control with computer assistance. A combination of hardware and software technologies was applied to prototype automated functions of the machine. Field tests demonstrated that remote control of concrete surface grinding is feasible and can be utilized as a semi-automated scheme on actual construction sites.First published online: 23 Jun 2016